2012
DOI: 10.4103/1817-1745.106468
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal epilepsy in chronic recurrent abdominal pain

Abstract: Background:Abdominal epilepsy (AE) is an uncommon cause for chronic recurrent abdominal pain in children and adults. It is characterized by paroxysmal episode of abdominal pain, diverse abdominal complaints, definite electroencephalogram (EEG) abnormalities and favorable response to the introduction of anti-epileptic drugs (AED). We studied 150 children with chronic recurrent abdominal pain and after exclusion of more common etiologies for the presenting complaints; workup proceeded with an EEG. We found 111 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Peppercorn and Herzog (9) used phenobarbital, phenytoin, valproic acid, and carbamazepine in their patients. Anticonvulsant drugs are recommended for all patients (for a maximum of 2 years) until their complaints have disappeared or EEG has returned to normal (5). EEG alone is not decisive in these patients, and it is important to correlate the findings with the clinical status (10).…”
Section: Discussionmentioning
confidence: 99%
“…Peppercorn and Herzog (9) used phenobarbital, phenytoin, valproic acid, and carbamazepine in their patients. Anticonvulsant drugs are recommended for all patients (for a maximum of 2 years) until their complaints have disappeared or EEG has returned to normal (5). EEG alone is not decisive in these patients, and it is important to correlate the findings with the clinical status (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs, either singly or in combination, have been used in management. Kshirsagar et al [12] and Dutta et al [7] found that oxcarbazepine significantly reduced the symptoms in patients. Yunus et al [13] reported that valproic acid treatment in the abdominal epilepsy like this case rapidly improved their patient's abdominal symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Recurrent abdominal pain may also be seen in visceral hyperalgesia, peptic ulcer disease and abdominal migraine [14,15]. The most common differential diagnosis for AE is abdominal migraine as they have many overlapping features.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Patients may have normal EEG patters in the inter-ictal periods and diagnosis must not be purely based on an EEG [15].…”
Section: Discussionmentioning
confidence: 99%